Analisis Pengaruh Return on Equity, Earning Per Share, dan Debt to Equity Ratio Terhadap Return Saham Perusahaan Sub Sektor Property & Real Estate yang Terdaftar di BEI - admin, LEON DA MAMBANG B11109066 (Jurnal Manajemen Update, 2016)
Capital Market as a means to channel funds from the public to various sectors in the form of investment. Investors need a sense of security for their investment. The investors who will make investment in the capital market by purchasing shares of the company will perform analysis of conditions in advance so their investment will yield return. Gaining return is the main purpose of trading activities in the capital market. This research aim to analyze the effect of Return on Equity (ROE), Earning Per Share (EPS), and Debt to Equity Ratio (DER) on stock returns of the property and real estate companies listen on the Indonesia Stock Exchange (IDX) from 2010 to 2014 The data were obtained from the Monthly Statistics of the Indonesia Stock Exchange (IDX), and the Indonesian Capital Market Directory (ICMD) in the period from 2010 to 2014. The population was 45 Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) and after the stage of purposive sampling, the samples were 15 companies. The analysis technique used in this research was multiple linear regression. The findings shows that only Earning Per Share (EPS) variable had a positive significant effect on stock returns. While Return on Equity (ROE), and Debt to Equity Ratio (DER) variables had no significant effect on stock returns. Keywords: Deb to to Equity Ratio (DER), Earning Per Share (EPS), Return on Equity (ROE), stock return